Study on Thermal Stability and Non-Isothermal Crystallization Behaviour of Polyethylene/Clay Nanocomposites. Issue 8 (October 2015) - He, Fu-An; Zhang, Li-Ming
In this work, thermal stability and non-isothermal crystallization behaviour of polyethylene/clay nanocomposites prepared by in-situ polymerization were studied. The thermal degradation kinetics of polyethylene/clay nanocomposites in nitrogen was investigated by a pseudo-first order method indicating that the addition of clay filler in polyethylene matrix could improve the thermal stability of nanocomposites. The Ozawa, Avrami, and modified Avrami-Ozawa methods were applied to study the non-isothermal crystallization behaviour of polyethylene/clay nanocomposite. It was found that the clay filler not only acted as a heterogeneous nucleation for the crystallization of polyethylene but also hindered the transport of the polyethylene molecule chains at the same time, resulting in a decrease of the crystallization growth rate of polyethylene with clay loading. In addition, the nucleation activity and the activation energy for the crystallization of polyethylene/clay nanocomposites were also estimated.